Current Advances in Delivery of Biotherapeutics Across the Blood-Brain Barrier - Rajadhyaksha, Manoj; Boyden, Tracey; Liras, Jennifer; El-Kattan, Ayman; Brodfuehrer, Joanne (Current Drug Discovery Technologies, 2011)
Significant efforts through genomic approaches have been dedicated toward the identification of novel proteinprotein interactions as promising therapeutic targets for indications such as Alzheimer's disease, Parkinson's disease and neuropsychiatric disorders. Additionally, the number of biotherapeutic agents entering the Pharmaceutical sector continues to increase and according to EvaluatePharma's “World Preview 2014” report, “the compounded annual growth rate of biologics is expected to be 8.5 percent from 2008-2014, eight to 10 times greater than the growth rate of small molecules”. However, there are limited examples of success in developing biotherapeutic modalities for central nervous system (CNS) diseases in the drug development pipeline. A primary reason for the lack of application of biotherapeutics to neuroscience targets, is that the blood-brain barrier (BBB) isolates and protects CNS structures creating a unique biochemically and immunologically privileged environment, therefore passage of macromolecules across this barrier has additional challenges. An understanding of the anatomical and physiological properties of this barrier with respect to penetration of biotherapeutics is presented in this review document. In this summary, recent advances in biotherapeutic delivery mechanisms across the BBB including transcranial brain drug delivery, focused ultrasound technology, nasal delivery, absorptive endocytosis, and receptor mediated endocytosis are evaluated using an industrial perspective. With acknowledgement that each approach has advantages and disadvantages, this review discusses the opportunities and challenges that are encountered during application of these methods across a variety of therapeutic areas such as, pain, obesity, neuroscience, and oncology. Utilizing an industrial perspective, including consideration of cost of goods and commercial feasibility for these approaches, this review highlights technology features which would enable industry investments toward novel BBB delivery technologies for biologics. Through continued development and improvement of such technology, new therapeutic options to treat and potentially cure central nervous system diseases could eventually evolve.
Keywords: nanotechnology